Processos fisiológicos limitantes à precocidade de Ricinus communis L.. - Olinto, Fabíola Vanessa de França Silva (2017)
The castor bean is a tropical oleaginosa whose productivity is impacted by edaphoclimatic factors. The study of foliar physiology, an organ that make important metabolic roles in the crop, besides photosynthesis, can provide subsidies for better management practices. The objective of this research was to examine the time of life of the castor leaf, its relation with the photosynthetic rate and the impact of this on the accumulation of carbohydrates in the seed. The experiment was conducted in a Vegetation House at Embrapa Algodão, with cultivated of 12 vase of cultivate BRS Energia in a completely randomized design. As each leaf was emitted and reached 5 cm of expansion in the main vein, it was identified and it was collected out daily readings of leaf area (up to constant area), insertion height in the stem (on the first day of the expansion) and daily, SPAD index, gas exchange and leaf age until senescence. The emission of the first racemus was identified. For destructive collection, a second experiment was set up with the same descriptions for the first, collecting the entire plant and separating it in root, stem and leaves every five days, from 10 to 120 days after emergence. Each vase was used for two crop cycles, the second being cultivated after the first one. The material was oven dried at 80°C for 72 hours, weighed and ground, to obtain the data of soluble sugars, starch content and total carbohydrates by the perchloric acid method. The castor leaf presented 53 days of life, on average, with very variable longevity, from 5-88 days, in the entire crop cycle. For the photosynthetic rate, the following variables were identified, in order of importance: the temperature, whose best performance was at 28ºC, being possible to increase it to 30ºC; Leaf age, from 6-14 days, corresponding to the period of leaf expansion; time of day until 3:00 p.m.; SPAD index, above 44. Peaks of soluble sugars, starch and total carbohydrates were identified in the stem, particularly between the flowering period and complete emission of the first bunch, and the end of the 120 days cycle.